From encyclopaedic project to editorial practice: the autochrome collection of the Árchives de la Planète´ - Toubert, Diane (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
This paper pretends to inquire about the encyclopedic nature of the 'Archives de la planete' (1908-1932), one of the biggest Autochrome collections in the world. Indeed, its constitution appears to be more empirical than systematic. Furthermore, besides gathering documentation of foreign countries, this project builds up the personal and national image of its founders.